Mind Mapping Strategy in Writing Descriptive Text Implemented to Ninth Grade Students - David Reynaldi Hambali (The Study Program of English Education of Palangka Raya University, 2021)
The research was conducted to find out the effect of using mind mapping strategy on students’ skill in writing descriptive text. The sample was 44 ninth grade students of SMP Sarunai Hulu Tampang by deciding class IX A as experimental group and class IX B as control group which were equally filled by 22 students to each group. The method used in this study was true experimental method, by using posttest-only control group design. The writer collected the data by conducting essay test of writing descriptive text. The writer also gave questionnaire as an additional instrument to support the data of the students in writing descriptive text. The data were analyzed using Mann-Whitney statistic since the data were not conform to the normal distribution. The result of this study showed that Asymp. Sig (2-tailed) was 0.000 which was lower than 0.05. This means there is a significant effect of using mind mapping strategy on students’ skill in writing descriptive text. Meanwhile, the result of the questionnaire showed that students’ response toward mind mapping strategy on students’ writing descriptive text was really good and positive. The students admitted that the using mind mapping strategy in English learning process could help them more easier to understand descriptive text. Also, the mind mapping was interesting and fun.